A tale of two parties: comparing the intensity of face threats in the democratic and republican primary debates of 2012 and 2016. (3rd April 2018) - Hinck, Shelly S.; Hinck, Edward A.; Dailey, William O.; Hinck, Robert S.; Hansen, Elizabeth; Madsen, Bradley
ABSTRACT: Using Politeness Theory as the theoretical lens, we explore how Hillary Rodham Clinton overcame a tough primary race against Bernie Sanders while Donald J. Trump emerged unexpectedly from a large field of experienced and highly qualified candidates to win the Republican nomination for president. We examine the degree of aggression and support of candidates' image in the messages exchanged in the primary debates along the lines of disagreement over character, policy, use of data, and campaign tactics. The results suggest that Republican candidates in their primary debates relied more on aggressive discourse strategies to appeal to partisan voters than Democrats; Democratic candidates were more supportive of one another while debating their differences than Republicans in the primary debates. The trend across two presidential election cycles suggests that primary debates are featuring more aggression, at least for Republicans, and it also appears that voters may be responding favorably to the strategy, at least in the most recent presidential campaign.